2006
DOI: 10.1002/bit.20743
|View full text |Cite
|
Sign up to set email alerts
|

Control of continuous polyhydroxybutyrate synthesis using calorimetry and flow cytometry

Abstract: The substrate-carbon flow can be controlled in continuous bioreactor cultures by the medium composition, for example, by the C/N ratio. The carbon distribution is optimal when a maximum fraction flows into the desired product and the residual is just sufficient to compensate for the dilution of the microbial catalyst. Undershooting of the latter condition is reflected immediately by changes in the Gibbs energy dissipation and cellular states. Two calorimetric measurement principles were applied to optimize the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…In more recent times it has been demonstrated that the problem associated with biotechnology cannot only be alleviated by scaling the instrument up to the bench scale, but rather by scaling it down to yield a chip calorimeter [31][32][33][34]. The principle of this device, shown in Figure 5, consists in measuring either the adiabatic temperature increase that results from a reacting mixture in a sample injected into the measuring cell, or the steadystate temperature during continuous flow of sample as compared with the temperature obtained from a continuous flow of reference sample.…”
Section: Calorimetric Measuring Techniquesmentioning
confidence: 99%
“…In more recent times it has been demonstrated that the problem associated with biotechnology cannot only be alleviated by scaling the instrument up to the bench scale, but rather by scaling it down to yield a chip calorimeter [31][32][33][34]. The principle of this device, shown in Figure 5, consists in measuring either the adiabatic temperature increase that results from a reacting mixture in a sample injected into the measuring cell, or the steadystate temperature during continuous flow of sample as compared with the temperature obtained from a continuous flow of reference sample.…”
Section: Calorimetric Measuring Techniquesmentioning
confidence: 99%
“…Recently, a growing number of studies have succeeded in monitoring the heat dissipation of microbial during fermentation by ITC [33][34][35][36][37]. Kemp and his colleagues [23,24] had combined a bioreactor with a flow microcalorimeter to monitor the heat flow rate of the growth of animal cells under the controlled conditions for long cultivation time.…”
Section: Resultsmentioning
confidence: 99%
“…Liquid cultures in flow calorimeters can easily deplete the dissolved oxygen or achieve toxic concentrations of products in the flow line between the culture vessel and the calorimetric vessel [48]. However, use of a flow loop from a bioreactor to a flow calorimeter can be of great value for bioprocess control [54]. When a gas is flowed through or over the system to maintain gas concentrations, great care must be taken to match the water vapor pressure in the input gas to the water vapor pressure over the culture, tissue, or organism.…”
Section: Metabolic Ratesmentioning
confidence: 99%
“…High-pressure ampules are available for most temperature-scanning calorimeters for determination of the effect of pressure on metabolism. Some large volume ( ‡1 l) calorimeters can be instrumented as chemostats for growth of microorganisms in liquid culture, or a regular chemostat can be connected via a flow line to a calorimeter [48,54]. Calorimeters suitable for small animals such as mice and rats are not included in this discussion, but are easily constructed [62].…”
Section: Metabolic Ratesmentioning
confidence: 99%